2017
DOI: 10.1007/s11150-017-9379-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of grandparenting in early childcare and child outcomes

Abstract: Early Child Care and Child Outcomes: The Role of Grandparents *In this paper, we focus on the impact of early grandparents' care on child cognitive outcomes, in the short and medium term, using data from the Millennium Cohort Study (UK). Compared with children looked after in a formal care centre, children cared by grandparents (as well as parents) are better in naming objects, but worse in tests concerning basic concepts development, problem-solving, mathematical concepts and constructing ability. In order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Similarly Del Boca et al . (2017) reported that only 3.2 per cent of mothers had moved to be nearer their family or friends in the two years surrounding the birth of a child and 1.2 per cent had moved in with family, based on analysis of the British Household Panel Survey. Further confidence in the validity of the instrument comes from controls of educational attainment and mother's age which could be related to mothers living close to the maternal grandmother and also directly affect the outcome of mothers’ employment decisions (see Del Boca et al ., 2017).…”
Section: Variablesmentioning
confidence: 99%
“…Similarly Del Boca et al . (2017) reported that only 3.2 per cent of mothers had moved to be nearer their family or friends in the two years surrounding the birth of a child and 1.2 per cent had moved in with family, based on analysis of the British Household Panel Survey. Further confidence in the validity of the instrument comes from controls of educational attainment and mother's age which could be related to mothers living close to the maternal grandmother and also directly affect the outcome of mothers’ employment decisions (see Del Boca et al ., 2017).…”
Section: Variablesmentioning
confidence: 99%
“…Provision of universal, cost-free and high-quality childcare has potential to reduce inequalities in children's outcomes, giving all children a stable, nurturing and educationally stimulating setting. Several studies have shown that centre-based childcare yields greater cognitive and academic benefits for children from socio-economically disadvantaged families ( Bradley & Vandell, 2007 ; Del Boca et al, 2018 ; Melhuish et al, 2015 ; van Huizen & Plantenga, 2018 ). Evidence in relation to socio-emotional outcomes is more mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Differential benefits of non-centre care are also uncertain. Non-centre care by grandparents can buffer against disadvantage ( Akhtar et al, 2017 ; Barnett et al, 2010 ; Silverstein & Ruiz, 2006 ), and can be especially beneficial where there is only one resident parent ( Attar-Schwartz et al, 2009 ), but has also been shown to exacerbate socioeconomic inequalities in cognitive development ( Del Boca et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Provision of universal, cost-free and high-quality childcare has potential to reduce inequalities in children’s outcomes, giving all children a stable, nurturing and educationally stimulating setting. Several studies have shown that centre-based childcare yields greater cognitive and academic benefits for children from socio-economically disadvantaged families [9, 12, 14, 11]. Evidence in relation to socio-emotional outcomes is more mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Differential benefits of non-centre care are also uncertain. Non-centre care by grandparents can buffer against disadvantage [17-19], and can be especially beneficial where there is only one resident parent [20], but has also been shown to exacerbate socioeconomic inequalities in cognitive development [14].…”
Section: Introductionmentioning
confidence: 99%